LANGUAGE APTITUDE AND LISTENING COMPREHENSION: A STUDY OF EFL STUDENTS’ PERFORMANCE - Stefani, Inggrit; Indrasari, Nunun; Suryawati, Sri Suci (Elite : English and Literature Journal, 2025)
The present research investigates the connection between students’ language aptitude and their listening comprehension and further examines which specific aptitude components are most closely linked to listening performance. In order to address these objectives, a quantitative correlational design was employed. This research involved seventy-two participants from a Senior High School, selected randomly by clusters to minimize the bias potential. The data were collected through two instrument tests; LLAMA Aptitude Test and Self-made Listening comprehension test that were administered to the participant in two different sessions. The results of those tests were then analyzed by using Spearman’s rho correlation, as the data did not follow a normal distribution. The results from the analysis demonstrated a moderate, yet significant, positive association between language aptitude scores and listening comprehension, with a coefficient of .441. Furthermore, among the four subtests, sound recognition (LLAMA D) and grammatical inference (LLAMA F) showed significant correlations with listening comprehension, while sound symbol recognition (LLAMA E) showed a weak yet still showed significant correlation with listening. However, vocabulary learning (LLAMA B) did not demonstrate a meaningful relationship. These findings suggest that successful listening comprehension relies more heavily on phonological and grammatical processing skills rather than simple vocabulary memorization. The findings offer practical insights for language teaching, emphasizing the need to develop learners’ sound processing and grammar inference abilities to improve listening skills.